Prevalence of Intestinal Parasitosis in Children of a Primary School in Pedro Juan Caballero - PY - Delgado do Amaral, Kayque Wellek; Garlet, Cristiane Venturini; Júnior, Daniel Contreira; Gomes da Silva, Marcus Tadeu Fernandes; Cogorno, Laura Simões; Lorenzoni Brandão, Luiz Eduardo; Marciano, Danilo Pigosso; Militão da Silva, João Miguel; Manfredini, Rebecca Corrêa; Fortaleza de Melo, João Italo (International Journal of Innovative Research in Medical Science, 2020)
Introduction: Parasitosis is a type of endoparasitism, which is directly related to sanitary conditions and is an important public health problem in developing countries. Objective: To determine the prevalence of intestinal parasites in children attending a primary public school in Pedro Juan Caballero - PY. Materials and Methods: 85 (eighty-five) stool samples were analyzed using the centrifugal sedimentation technique. Results: Cysts and/or parasite eggs were observed in the stool samples of 67 (78.8%) children. Giardia lamblia cysts were those that showed the highest incidence in the children. Conclusion: The high Giardia lamblia index demonstrates the lack of access to drinking water for consumption, inadequate sanitation and the absence of a public health network. This study highlights the importance of encouraging the use of serial analysis of stool, strengthening preventive measures for parasitosis, developing protocols for their approach, and designing a strategy that includes the preschool population in the programs that periodically evaluate the development of children.